SHARED PERSPECTIVES: PARTICIPATORY PHOTOGRAPHY AND VISUAL ANTHROPOLOGY IN THE USE OF PHOTOVOICE - Néres, Daniel Ercílio; Keller, Daniel; Schemes, Claudia (Seven Editora, 2025)
This article discusses Photovoice as a methodological practice situated within the field of visual and shared anthropology, oriented toward the collaborative production of knowledge and the understanding of life worlds shaped by intersectional identities. Drawing on an empirical experience conducted with seven participants of diverse profiles — including individuals with visual impairments — the study analyzes the process of image production, interviews, and collective meetings, examining how photography can operate simultaneously as an ethnographic artifact, an enunciative device, and a space of collective care. The methodological steps included media literacy, free image production, individual pre-selections, discussion groups, and analytical feedback sessions, with emphasis on accessibility and ethical reflexivity. The analysis of the images and narratives revealed tensions between visibility and protection, agency and vulnerability, highlighting the political and sensorial potency of the image as a space of negotiation and encounter. The work is situated within the tradition of shared anthropology and within decolonial and multisensory epistemologies, proposing a reading of photography as a gesture of sharing and an instrument of symbolic resistance. DOI: https://doi.org/10.56238/sevened2025.036-061